Analysis of 21 autosomal STRs in Saudi Arabia reveals population structure and the influence of consanguinity. (March 2019) - Khubrani, Yahya M.; Wetton, Jon H.; Jobling, Mark A.
Highlights: GlobalFiler (21-STR) genotypes reported for 523 Saudi Arabian males. Significant differences in allele frequencies among five geographical sub-regions. Heterozygote deficiency observed at nearly all loci in all regions, likely reflecting history of consanguineous marriage. Autosomal sub-regional pattern contrasts with previously described pattern of Y-STR variation in the same samples. Population structure and heterozygote deficiency should be accounted for in forensic interpretation of Saudi STR profiles. Abstract: Variation in the 21 autosomal STRs detected by the GlobalFiler multiplex was investigated in a sample of 523 indigenous male Arabs from five geographic regions of Saudi Arabia. Although allele frequencies for the entire dataset were found to be broadly similar to those determined in previous studies of Saudi citizens, significant differences were found among regions. Heterozygote deficiency was observed at nearly all loci in all regions, probably as a consequence of high levels of consanguineous marriage; in the case of D2S1338, which showed the largest deviation from Hardy-Weinberg equilibrium, the presence of a null allele also played a part. Genetic distances were greatest between the Northern and Southern regions, whilst the West, Central and East appeared most similar to each other, and to previously published surveys. This contrasts with previously described variation among paternal lineages in the same sample-set: Y-chromosome variation was limited within the North/Central/South core compared with the more diverse East and West. Differences between autosomal and Y-chromosomal patterns may reflect genetic drift on the Y chromosome, exacerbated by prevalent patrilineal descent groups in different regions.